Testing the waters: the limits of consequentialist logic in Australia's asylum seeker debate. Issue 1 (2nd January 2019) - Dellora, Carlo
ABSTRACT: This work takes existing justifications for Australian asylum seeker policy at face value. For the past five years now both major parties have articulated themselves using the rhetoric of consequentialism, arguing that the policies of offshore detention and boat turn backs are all about securing the safety of refugees. This work puts the personal opinions of each member of parliament aside and examines whether these rhetorical justifications are internally consistent. What will become clear is that the utilitarian framework used in this debate does not sit on terra firma . Rather, its foundations lead to conclusions many might find uncomfortable – suggesting that existing theoretical justifications for Australian asylum seeker policy are ultimately implausible.